Penilaian Risiko Pohon berbasis Visual Tree Assessment pada Jalur Hijau Kota Mataram: Tree Risk Assessment based on Visual Tree Assessment on Green Lane of Mataram City - Kahirunnisa, Aliefia Shatila Diva; Wahyuningsih, Endah; Indriyatno, Indriyatno (HUTAN TROPIKA, 2025)
This study evaluated the health of trees in the green belt of Mataram City with a focus on root, stem and crown conditions. The research, which took place from December 2024 to February 2025, aimed to identify at-risk trees and develop effective protection strategies to reduce damage to the city's green belt. The Visual Tree Assessment (VTA) method was used to collect data, based on the International Society of Arboriculture (ISA) criteria. The research findings emphasize environmental impacts on tree health, including urban activities and extreme weather. This research emphasizes the importance of public education to improve the resilience of urban ecosystems and reduce the risk of tree-related incidents, as well as contributing to urban planning and environmental management to ensure the sustainability of green spaces in Mataram.